The Effect of Skipping Training on Jump Smash Ability in Badminton Games at PB Topaz Palembang - Grace Kharisma Tambunan; Jujur Gunawan Manullang (Universitas Negeri Semarang, 2023)
Research on stroke in the badminton game of PB topaz Palembang athletes has not been carried out optimally so that the right training method is needed, namely skipping training. The research method uses the pre-experimental design method with the One Group Pretest-Posttest Design research design. Data collection techniques use tests and measurements. The sample in this study amounted to 22 athletes. The data analysis techniques used in this study are normality test, homogeneity test and paired sample t-test. The results of the analysis showed that there was a significant influence of skipping training on jump smash ability in badminton games at PB topaz Palembang with the results of hypothesis testing of the skipping training group proving that Sig. (2-tailed) 0.000 ≤ α (α = 0.025), then H0 was rejected.